Effectiveness of the Pfizer-BioNTech and Oxford-AstraZeneca vaccines on covid-19 related symptoms, hospital admissions, and mortality in older adults in England: test negative case-control study. (13th May 2021) - Lopez Bernal, Jamie; Andrews, Nick; Gower, Charlotte; Robertson, Chris; Stowe, Julia; Tessier, Elise; Simmons, Ruth; Cottrell, Simon; Roberts, Richard; O'Doherty, Mark; Brown, Kevin; Cameron, Claire; et al.
Abstract: Objective: To estimate the real world effectiveness of the Pfizer-BioNTech BNT162b2 and Oxford-AstraZeneca ChAdOx1-S vaccines against confirmed covid-19 symptoms (including the UK variant of concern B.1.1.7), admissions to hospital, and deaths. Design: Test negative case-control study. Setting: Community testing for covid-19 in England. Participants: 156 930 adults aged 70 years and older who reported symptoms of covid-19 between 8 December 2020 and 19 February 2021 and were successfully linked to vaccination data in the National Immunisation Management System. Interventions: Vaccination with BNT162b2 or ChAdOx1-S. Main outcome measures: Primary outcomes were polymerase chain reaction confirmed symptomatic SARS-CoV-2 infections, admissions to hospital for covid-19, and deaths with covid-19. Results: Participants aged 80 years and older vaccinated with BNT162b2 before 4 January 2021 had a higher odds of testing positive for covid-19 in the first nine days after vaccination (odds ratio up to 1.48, 95% confidence interval 1.23 to 1.77), indicating that those initially targeted had a higher underlying risk of infection. Vaccine effectiveness was therefore compared with the baseline post-vaccination period. Vaccine effects were noted 10 to 13 days after vaccination, reaching a vaccine effectiveness of 70% (95% confidence interval 59% to 78%), then plateauing. From 14 days after the second dose a vaccination effectiveness of 89% (85% to 93%) was found compared with the increased baseline risk. Participants aged 70 years and older vaccinated from 4 January (when ChAdOx1-S delivery commenced) had a similar underlying risk of covid-19 to unvaccinated individuals. With BNT162b2, vaccine effectiveness reached 61% (51% to 69%) from 28 to 34 days after vaccination, then plateaued. With ChAdOx1-S, effects were seen from 14 to 20 days after vaccination, reaching an effectiveness of 60% (41% to 73%) from 28 to 34 days, increasing to 73% (27% to 90%) from day 35 onwards. On top of the protection against symptomatic disease, a further 43% (33% to 52%) reduced risk of emergency hospital admission and 51% (37% to 62%) reduced risk of death was observed in those who had received one dose of BNT162b2. Participants who had received one dose of ChAdOx1-S had a further 37% (3% to 59%) reduced risk of emergency hospital admission. Follow-up was insufficient to assess the effect of ChAdOx1-S on mortality. Combined with the effect against symptomatic disease, a single dose of either vaccine was about 80% effective at preventing admission to hospital with covid-19 and a single dose of BNT162b2 was 85% effective at preventing death with covid-19. Conclusion: Vaccination with either one dose of BNT162b2 or ChAdOx1-S was associated with a significant reduction in symptomatic covid-19 in older adults, and with further protection against severe disease. Both vaccines showed similar effects. Protection was maintained for the duration of follow-up (>6 weeks). A second dose of BNT162b2 was associated with further protection against symptomatic disease. A clear effect of the vaccines against the B.1.1.7 variant was found.